Anaesthesia and anaesthesiologist speciality's knowledge assessment of paramedics in armed forces hospital: a questionnaire study - Kamewad, Amit Kumar; Sharma, Shambhu Prasad; Eapen, Sunny; Gupta, Tarun (International Journal of Research in Medical Sciences, 2021)
Background: Science of anaesthesia has revolutionized from traditional only application of relieving patient from pain induced during surgery to wide spectrum approaches like palliative care, critical care, perioperative care along with pain management. Despite of such critical roles in health care sector there is still a lack of awareness about anaesthesiology and anaesthesiologists. Current investigation was aimed towards assessing the awareness of paramedical staff regarding the role of anesthesiology. Methods: Current investigation was a prospective cross-sectional questionnaire-based study conducted on 100 paramedical staff posted in different departments of military hospital Jaipur. All the study participants were interviewed face to face orally by an investigator using the set of questions listed in the questionnaire. Participants responses were documented and statistically represented as percentage. Results: Current study findings reveal that even though majority of the study participants (91) had experience more than 5 years in the hospital and most of them (˃90%) of participants were having educational level of higher secondary or graduation still the role of anaesthesiologist outside operation theatre was poorly known to paramedical staff. It was also observed in current investigation that role of anesthetist in pain clinic was poorly known to most of the participating paramedical staff. Conclusions: Providing knowledge about expertise of anesthesiologist among paramedical staffs by incorporating anaesthesia in the curriculum, in house training programs, use of pamphlets, internet and other easily assessable techniques is highly desirable for spreading awareness of anaesthesia and anesthetist among paramedical staff, so that patient can avail anaesthesia related services effectively.